2008
DOI: 10.1155/2008/901250
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Colorectal Computed Tomography Abnormalities: Would You Send every Patient for a Colonoscopy?

Abstract: METHODS: Ninety-four consecutive patients found to have largebowel abnormalities on abdominal CT were referred for colonoscopy. Of these patients, 48 were referred for a suspected colorectal tumour and 46 for CRWT. Colonoscopy was performed and findings were compared. RESULTS: Of the 48 suspected colorectal tumours, 34 were determined to be neoplastic lesions on colonoscopy. Of these, 26 were malignant and eight were benign. Colonoscopy revealed no abnormality in 30 of 46 patients with CRWT as a solitary findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
(5 reference statements)
1
14
0
Order By: Relevance
“…In our study, the thickness of normal colonic wall was <3 mm. Our data were consistent with previous results (15). A threshold value for colonic wall thickness has not been determined for the diagnosis of CRC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the thickness of normal colonic wall was <3 mm. Our data were consistent with previous results (15). A threshold value for colonic wall thickness has not been determined for the diagnosis of CRC.…”
Section: Discussionsupporting
confidence: 92%
“…W, wall thickening; M, mass. Stermer et al performed colonoscopy in patients who had a wall thickened to >3 mm (15). Of the 46 patients, 30 had a wall thicker than 3 mm, but showed no abnormalities, suggesting that false-positive results may be found in patients with walls thicker than 3 mm; thus, the threshold value may be >3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…7 Stermer et al argued against the routine use of colonoscopy but agreed that high risk patients (family history, positive faecal occult blood, age >50 years) with incidental BWT would benefit. 8 In the present study, lesions affecting the caecum and ascending colon on CT were least likely to yield abnormal findings on endoscopy (48.4%) compared with left-sided lesions (62.4%). This confirms the results of Cai et al 9 They showed an 81% correlation with rectosigmoid lesions but only a 13% correlation with caecal lesions in patients with CT reports of BWT.…”
Section: Methodsmentioning
confidence: 44%
“…[2][3][4][5][6][7][8][9][10][11][12] In addition, several reports in the literature have attempted to differentiate benign and malignant cases of BWT. [13][14][15] These studies are relatively small and, as yet, no consensus has emerged on how this issue should be tackled.…”
Section: General Surgerymentioning
confidence: 99%
“…In 71% of patients, tumorous lesions were found, whereas in 26 patients, these lesions were malignant. According to this study result, the authors recommend further endoscopy when bowel wall thickening occurs simultaneously with further risk factors such as positive family history or positive fecal occult blood test [8].…”
Section: Discussionmentioning
confidence: 82%